Bantuan Sistem Komputasi Aljabar Bagi Pembelajaran Fisika Terapan di Politeknik - Sardjito Sardjito (Indonesian Journal of Physics, 2002)
Applied Physics Teaching in Polytechnics as a part of professional education should have orientation towards dailly practical problems. Usually such problems need more complicated calculations for solving than ideal problems. We can not use simple analytical calculations to solve the problems. The aid of a Computational Algebra System in those cases will be helpful. One kind computational algebra system which is used in Polytechnics is an application software called Derive for Windows. Derive is a mathematical computer program, which can do both symbolic and numeric computations. These can also be visualized with graphics capabilities. This program eliminates the drudgery of long mathematical calculations thus giving students the chance of interpreting and analyzing the problems more intensively. The examples about parabolic motion and damped vibration are described in this paper